Penerapan Model Pembelajaran Maharah Qiraah Untuk Meningkatkan Minat Murid dalam Belajar Bahasa Arab di Desa Bungbaruh Kadur Pamekasan - Hamdy, Mohammad Zainal; Ningsih, Wiwik Prasetiyo; Khumairoh, Khumairoh (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
Arabic language learning faces various challenges with the very rapid development of the era. As an Arabic language teacher, you need to have an interesting and effective model so that students prefer to learn Arabic. The aim of this research is to make students like Arabic more by introducing various models that attract students' interest in learning Arabic, especially at Nadhatun Nasyiin Kadur Pamekasan. Using qualitative research, the researcher describes descriptively the learning model for reading reading skills to increase students' love and liking for language. The results of this research show a tendency for students to have higher and increased interest and enthusiasm in Arabic language learning activities with various models including tartib al-nash wa al-kalimah, tartib al-hiwar, and tasykil al-nash.